2016
DOI: 10.1111/1475-6773.12642
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Distinguish High‐Performing Accountable Care Organizations in the Medicare Shared Savings Program

Abstract: Shorter interventions can improve ACO performance-use of embedded care coordinators and local, regional health information systems; timely feedback of performance data. However, longer term interventions are needed to promote physician-hospital collaboration and skills of physician leaders. CMS and other stakeholders need realistic timelines for ACO performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…2223 Common changes include improving access to appointments, developing team based models of primary care, coordinating services between care settings, and using data to support care redesign. These changes will feel familiar to many in the NHS.…”
Section: How Are Acos Redesigning Care?mentioning
confidence: 99%
See 1 more Smart Citation
“…2223 Common changes include improving access to appointments, developing team based models of primary care, coordinating services between care settings, and using data to support care redesign. These changes will feel familiar to many in the NHS.…”
Section: How Are Acos Redesigning Care?mentioning
confidence: 99%
“…Broader evidence also suggests that organisational type is not associated with ACO outcomes 21. Internal organisational factors more to do with leadership, culture, and management—such as capabilities to redesign services or the ability to overcome professional inertia—offer alternative explanations for ACO performance 1323…”
Section: Lessons For the English Nhsmentioning
confidence: 99%
“…11 EHRs are an important means of managing and co-ordinating patient care for effective ACO performance; substance abuse treatment services' use of EHRs predicted how likely they were to participate in an ACO. 57 Other studies corroborate this pattern 63 (see also Chapter 6).…”
Section: Chaptermentioning
confidence: 70%
“…A study of six ACOs found that timely, consistent information about patients' admissions and discharge enabled the planning of follow-up services that patients might need within 30 days of discharge. 63 Two additional studies described individual projects that effectively used HIT to co-ordinate care in MCP-like contexts. The Gesundes Kinzigtal project reported improved patient and health-worker experience, and reduced costs and mortality.…”
mentioning
confidence: 99%
“…Since the beginning of the program, the number of ACOs operating in rural America has increased considerably . As CMS releases ACO performance data, it is critical to evaluate how rural ACOs’ performance compares to that of urban ACOs and what organizational attributes are associated with ACO performance to inform policy and practice . This paper contributes such knowledge by evaluating associations between geographic, structural, and service‐provision attributes of MSSP ACOs and the ACOs’ quality performance.…”
mentioning
confidence: 99%